PHENYTOIN-ASSOCIATED LYMPHOADENOPATHY MIMICKING A PERIPHERAL T-CELL LYMPHOMA - Lynn C. Moscinski; Mark E. Johns; Lubomir Sokol (Mediterranean Journal of Hematology and Infectious Diseases)
We report a case of phenytoin-induced pseudolymphoma in a 28-year-old male with a history of autism and seizure disorder. The patient presented with bilateral cervical lymphadenopathy that was shown to be moderately to markedly FDG-avid on a whole body PET/CT scan. Flow cytometry analysis of peripheral blood and bone marrow mononuclear cells detected identical T cell population with aberrant immunophenotype. Additionally, a TCR beta gene was found to be clonally rearranged in both peripheral blood and bone marrow supporting a clonal origin of atypical T cells. However, no such clonal population of T-cells could be detected in a pathologic specimen obtained from an excisional biopsy of one of the patient’s cervical lymph nodes. After discontinuing the patient’s phenytoin, his lymphadenopathy has nearly completely resolved and circulation clonal T cell population disappeared with 12 months of follow-up.